Meningkatkan Hasil Belajar Kimia dengan Pendekatan Kooperatif Melalui Demonstrasi dan Kelompok Belajar Terbimbing pada Siswa SMA Negeri 1 Takalar - Muhsin Muhsin (UNDIKMA, 2021)
This study aims to improve students' chemistry learning outcomes with a cooperative approach through demonstrations and guided study groups. This research method uses classroom action research with research subjects are students of class X IPA2 SMAN 1 Takalar, amounting to 35 people. This research was conducted in two cycles and each cycle was conducted in four meetings including a test at the end of each cycle. Data were collected using observations and tests. The data obtained were analyzed using quantitative analysis and descriptive statistics. The results showed that the chemistry learning outcomes of class X IPA2 students of SMAN 1 Takalar could be improved with a cooperative approach through demonstrations and guided study groups with an average value of 73.00 (high category), and based on the observation results showed an increase in the frequency of student attendance and student activeness in following the learning process.